2016
DOI: 10.1177/0022185616638096
|View full text |Cite
|
Sign up to set email alerts
|

Priced to care: Factors underpinning missed care

Abstract: This article examines missed care through dialogues examining the perceptions of nurses in regard to missed care occasions. Using a critical discourse analysis (CDA), the study explores the truth claims of participants who describe the challenges they encounter in daily attempts to deliver what they consider effective patient care. These are compared to the mandates of state and organisational policy prescribing clinical practice. The boundaries of tension that are expressed by nurses within the milieu of miss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 37 publications
1
23
0
Order By: Relevance
“…23 Rationing results in nurses not being able to carry out their core work, that is the provision of effective and safe care appropriate to patient need, based on a skilled clinical (as distinct from a financial) assessment. 24,25…”
Section: Confronting Rationing In Nursing Carementioning
confidence: 99%
See 1 more Smart Citation
“…23 Rationing results in nurses not being able to carry out their core work, that is the provision of effective and safe care appropriate to patient need, based on a skilled clinical (as distinct from a financial) assessment. 24,25…”
Section: Confronting Rationing In Nursing Carementioning
confidence: 99%
“…This has also been reflected in other studies, where nurses identified lack of time to carry out their work. 25,36 These findings suggest that we need to engage in discussion regarding allocation of the nursing resource (i.e. the number of nursing staff required at institutional and unit level, based on the dominant models of care delivery is use) and rationing in nursing.…”
Section: Confronting Rationing In Nursing Carementioning
confidence: 99%
“…Influences on the lack of continuity of care include increased pressure on staffing related to reduced human resource allocations and skills mix, and generalized cost constraints (Bergh, Friberg, Persson, & Dahlborg-Lyckhage, 2015;Chadban et al, 2010;Phelan & McCarthy, 2016). Additionally, in the work intensified environment, integrating care has been hampered by inadequate communication between departments/providers, poor or ineffective handover between services, and poor or absent discharge planning and patient education (Finlayson, Sheridan, Cumming, & Fowler, 2012;Harvey et al, 2016;Henderson, Willis, Toffoli, Hamilton, & Blackman, 2016;Willis et al, 2015). Often care gets missed, or misunderstood, and there are unnecessary duplications between services (Finlayson et al, 2012).…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…The same or very similar issues (i.e. insufficient human and material resources or lack of support) in addition to factors relating to the work environment itself are now recognized as the main predictors of missed nursing care (Aiken, Sloane, Bruyneel, Heede, & Sermeus, 2013; Harvey et al, 2016; Schubert et al, 2013).…”
Section: Introductionmentioning
confidence: 99%